Structural and thermal properties of Alkali-treated biomass fibers and W. robusta waste reinforced PLA hybrid biocomposites - Isma Dembri; Ahmed Belaadi; Abdelaziz Lekrine; Messaouda Boumaaza; Mohammad Jawaid; Ahmad Safwan Ismail; Djamel Ghernaout (Elsevier Ltd., 2025)
The aim of this study to develop biodegradable composites by using agricultural biowaste that well qualified to be used in various applications. They are an outstanding choice for the production of sports equipment, green building materials, and car interior components due to their transport and recycling capabilities. In this work, hybrid biocomposites are fabricated from a Poly lactic acid (PLA) matrix reinforced with alkali-treated Robusta (Rb) short biomass palm fibers and biochar (B) were characterized. Scanning electron microscopy showed a decrease in the interfacial spaces of the treated reinforcement materials compared to the untreated ones, becoming less frequent and smaller. The Rb-reinforced biocomposite treated with 3 % NaOH (PLA-BRb3) showed better viscoelastic behavior, with high energy storage and loss moduli and minimal damping factor (tan δ), showing high elasticity and low glass transition temperature. The loss and storage moduli reached 516 MPa and 2463.64 MPa, respectively, suggesting excellent energy dissipation and enhanced damping capacity, ideal for shock and vibration resistance applications. Tan δ decreased to 0.97, making it the most elastic material in the study. The qualities of these green biocomposites could be improved and their uses could be extended to various sustainable production sectors through further research and development.